2014
DOI: 10.1111/ahe.12111
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of PACAP with VIP, SP and CGRP in the Porcine Nodose Ganglion Sensory Neurons

Abstract: Our previous study revealed the expression of substance P (SP) and calcitonin gene-related peptide (CGRP) in sensory distal ganglion of the vagus (nodose ganglion) neurons in the pig. As these neuropeptides may be involved in nociception, the goal of these investigations was to determine possible expression of vasoactive intestinal polypeptide (VIP), SP and CGRP in the pituitary adenylate cyclase-activating polypeptide-immunoreactive (PACAP-IR) porcine nodose perikarya. Co-expression of these substances was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…The presence of PACAP in the jugular ganglion was described in the rat (Mulder et al 1995). Studies performed on the nodose ganglion in the pig have revealed that 67.25% of the neurones in the right, and 66.5% in the left ganglion express immunoreactivity to this peptide (Rytel L et al 2015), whereas the present study has established that in the porcine PGNV PACAP-IR neurones represent only 15% of all ganglionic nerve cells.…”
Section: Disscusioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The presence of PACAP in the jugular ganglion was described in the rat (Mulder et al 1995). Studies performed on the nodose ganglion in the pig have revealed that 67.25% of the neurones in the right, and 66.5% in the left ganglion express immunoreactivity to this peptide (Rytel L et al 2015), whereas the present study has established that in the porcine PGNV PACAP-IR neurones represent only 15% of all ganglionic nerve cells.…”
Section: Disscusioncontrasting
confidence: 42%
“…In the nodose and petrosal ganglia, only a few VIP-IR (Lundberg et al 1978, Helke and Hill 1988, Helke and Rabchevsky 1991, Zhuo et al 1997 or VIP mRNA-containing (Zhuo et al 1995) neurons can be detected. In the porcine sensory nodose ganglion, 40% of neurones exhibited immunoreactivity to VIP (Rytel L et al 2015), but only less than 20% VIP-positive nerve cells were observed in the vestibular ganglion (Dudek et al 2012).…”
Section: Disscusionmentioning
confidence: 93%
See 1 more Smart Citation
“…Till now not much is known whether and how PACAP and SP functionally interact in the pancreas so analogies to other ganglia would be of interest. At the periphery, the co-localization of SP and PACAP is frequently noted in 40-50% of sensory neurons (Rytel et al 2014). In the rat model of neurogenic inflammation, PACAP-38 released from afferent nerve terminals has been found to inhibit outflow of SP, somatostatin and calcitonin-gene related peptide (Nemeth et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery in 1989, PACAP has been an object of intense anatomical, physiological and pharmacological studies. Using immunohistochemical and radioimmunoassay techniques, the expression of PACAP and its receptors has been found in numerous mammalian tissues including neurons of the central and peripheral nervous system (Masuo et al 1991, Ghatei et al 1993, Csati et al 2012, Rytel et al 2014 as well as enteric Liu 2001, Miampamba et al 2002) and intramural ganglia of the pancreas (Hannibal and Fahrenkrug 2000) and heart (Girard et al 2007). At the central level, PACAP may exert a variety of functions like modulation of hypothalamic-pituitary hormones release (Kanasaki et al 2015), food consumption and water drinking (Puig de Parada et al 1995, Mounien et al 2009), neuronal differentiation, neuroprotection (Manecka et al 2013) and many more, whereas its role at the periphery is relatively less understood.…”
Section: Introductionmentioning
confidence: 99%